Keterkaitan Alat Tangkap Ikan dengan Jenis Ikan yang Didapatkan di Rawa Pening - Weri, Michael Natanael; Sucahyo, Sucahyo (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
Rawa Pening is a semi-natural lake and estuary of 16 rivers located in 9 sub-watersheds (watershed). Rawa Pening is a habitat of various types of freshwater fish, such as tilapia, koan, cork, catfish, wader, betutu, and mujair. In this research, inventory of fishing gear used by fishermen in Rawa Pening with Purposive Random Sampling method. Data from the caught fish species were observed directly and interviews with the respondents. The purpose of this study is to identify and inventory the methods and types of fishing gear used by the fishermen and the types of fish caught in the context of conservation. From the research conducted there is a link between fishing gear used with the type of fish caught in Rawa Pening. The catching tools commonly used in Rawa Pening are quite specific for some species of fish. The number of fish species commonly caught is 17 species of fish. For the three types of fish that have the highest percentage of caught various types of fishing gear is (Osteochilus hasselti) and tilapia (Oreochromis niloticus) 75% and fish cork (Channa striata) of 62.5%. The catching tools in Rawa Pening are classified as net gear net (gill net), branjang (lift net) and nets. Meanwhile, for fishing gear in the form of trap is bubu / icir. In addition, there are other fishing gear such as spear, fishing line, kere and so on. The net-type fishing gear is found in Rawa Pening waters and has a high average catch rate. Branjang and Kere belong to the highest fishing gear in catching various types of fish and less selective for catching fish. The introduction of introduced fish becomes another factor besides fishing gear against endemic fish population level in Rawa Pening.